The role of the electric sector in reducing social vulnerability (Research, Society and Development, 2022)
The study aims to understand the role of the electricity sector in reducing social vulnerability. Electric energy, through government actions within the electricity sector, has an important strategic role in promoting the process of human development. Deepening the understanding of the connections between electricity and social vulnerability will result in important subsidies for the decision-making process that tend to contribute to the reduction of social vulnerability, as an integral part of the human development process. The methodology of this study was limited to the theoretical field and used scientific journals that conceptually deal with the categories of electricity, social vulnerability and their theoretical relationships. The study concluded that the connections between electricity and social vulnerability are evident when investments in electricity consider aspects that favor the living conditions of populations, that is, when investments in electricity: enable the generation of new posts through production chains arising from new sources of generation of this input, provides opportunities for local populations to contribute to the decision-making process regarding their realities, favor the proper examination of the possible socio-environmental impacts generated with the populations affected by energy projects, and finance institutional regulation of electricity distributors.